Tom and Jerry. Blast off to Mars [videorecording (DVD)] - Bennett, Jeff (Jeff Glen); Burton, Corey; Fiore, Kathryn; Minton, Tom; Kopp, Bill; Bernstein, Steven R.; Bernstein, Julie; Hanna, William, 1910-2001; Barbera, Joseph (Warner Home Video, 2005)
Feckless feline Tom and his rodent rival, Jerry, get trapped in a spaceship and wind up on Mars, where the tiny locals attack Tom, thinking he is a giant space monster, and hail Jerry as their long-lost supreme leader.